Influence of Teacher Support and Personal Relevance on Academic Self-Efficacy and Enjoyment of Mathematics Lessons: A Structural Equation Modeling Approach - Aldridge, Jill; Afari, Ernest; Fraser, Barry (University of Alberta, 2012)
The purpose of our study was to examine the effects of two psychosocial features of the classroom environment (teacher support and personal relevance) on college students’ academic self-efficacy and enjoyment of mathematics lessons. Data collected from 352 mathematics students attending three higher education institutions in the United Arab Emirates were used to validate the questionnaires and to investigate the hypothesized relationships. Structural equation modeling analysis suggests that teacher support and personal relevance are influential predictors of enjoyment of mathematics lessons and academic self-efficacy.